Evaluasi Efektivitas dan Dampak Hibah UPLAND Kabupaten Lebak - Pramuji, Bambang Imam; Widjayanto, Wahyu; Heryuananto, Adhi Risya (Polytechnic of State Finance STAN, 2025)
This study evaluates the effectiveness and impact of the UPLAND Grant Program in Lebak Regency, which aims to enhance agricultural productivity and farmers’ income in upland areas through an integrated horticulture–livestock farming system. The research employs a mixed-methods approach, combining structured questionnaires for technical officers with focus group discussions (FGDs) involving local stakeholders to assess program benefits (outcomes and impacts) and implementation effectiveness along the input–activity–output chain.One of the key issues examined in this study is the reimbursement-based grant disbursement mechanism, which requires local governments to pre-finance program activities using their regional cash resources. This mechanism poses challenges in cash management and carries a risk of delayed implementation, as reimbursements can only be processed according to predetermined quarterly schedules stipulated. The results indicate a significant improvement in technical capacity and agricultural infrastructure, with nearly all farm roads, irrigation systems, seeds, livestock facilities, and farmer training successfully delivered. Farmers’ incomes have begun to increase through mangosteen production and diversification efforts with sheep farming, supporting food security and alternative income streams. However, the economic impact remains unstable due to seasonal production, inconsistent export quality, weak cooperative institutions, and the complexity of the reimbursement mechanism, which constrains regional cash liquidity. The study recommends simplifying administrative and cash planning procedures, strengthening post-harvest value chains and market access, empowering farmer, women, and youth organizations, and adopting digital monitoring and evaluation systems to support faster and more adaptive decision-making.